2007
DOI: 10.1016/j.stem.2007.05.018
|View full text |Cite
|
Sign up to set email alerts
|

The Renewal and Differentiation of Isl1+ Cardiovascular Progenitors Are Controlled by a Wnt/β-Catenin Pathway

Abstract: Isl1(+) cardiovascular progenitors and their downstream progeny play a pivotal role in cardiogenesis and lineage diversification of the heart. The mechanisms that control their renewal and differentiation are largely unknown. Herein, we show that the Wnt/beta-catenin pathway is a major component by which cardiac mesenchymal cells modulate the prespecification, renewal, and differentiation of isl1(+) cardiovascular progenitors. This microenvironment can be reconstituted by a Wnt3a-secreting feeder layer with ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
316
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(340 citation statements)
references
References 35 publications
(58 reference statements)
22
316
0
2
Order By: Relevance
“…Phase-contrast images of E18.5 embryos and hearts from WT and Tet3 KO mice showed no obvious developmental abnormalities of cardiac or other tissues. Nevertheless, qPCR and immunostaining analysis of the whole hearts from WT and Tet3 KO embryos (E18.5) showed an increase of the cardiac progenitor marker Isl-1, a target gene of Wnt/β-catenin signaling (44) in the Tet3 KO heart, especially in the right ventricle (Fig. S5).…”
Section: Phenotype Of Tet3-deficient Mescs Is Exacerbated By Concurrentmentioning
confidence: 99%
“…Phase-contrast images of E18.5 embryos and hearts from WT and Tet3 KO mice showed no obvious developmental abnormalities of cardiac or other tissues. Nevertheless, qPCR and immunostaining analysis of the whole hearts from WT and Tet3 KO embryos (E18.5) showed an increase of the cardiac progenitor marker Isl-1, a target gene of Wnt/β-catenin signaling (44) in the Tet3 KO heart, especially in the right ventricle (Fig. S5).…”
Section: Phenotype Of Tet3-deficient Mescs Is Exacerbated By Concurrentmentioning
confidence: 99%
“…32,33 Also, differentiation of Isl1 ϩ cardiac progenitors was inhibited by the addition of Wnt3a-conditioned media. 84 Interestingly, the above-mentioned overexpression of constitutively active ␤-catenin by use of a SHF-specific enhancer of the Mef2c gene resulted in massive accumulation of Isl1-positive progenitor cells attributable not only to increased proliferation but also to a massive inhibition of terminal differentiation. 84 A novel extracellular inhibitor of Wnt/␤-catenin signaling was identified recently as IGFBP-4 (insulin-like growth factors binding protein).…”
Section: Wnt Signaling During Terminal Differentiationmentioning
confidence: 99%
“…84 Interestingly, the above-mentioned overexpression of constitutively active ␤-catenin by use of a SHF-specific enhancer of the Mef2c gene resulted in massive accumulation of Isl1-positive progenitor cells attributable not only to increased proliferation but also to a massive inhibition of terminal differentiation. 84 A novel extracellular inhibitor of Wnt/␤-catenin signaling was identified recently as IGFBP-4 (insulin-like growth factors binding protein). In Xenopus, it was shown that IGFBP-4 binds to Frizzled and LRP6, thereby preventing binding of a Wnt ligand.…”
Section: Wnt Signaling During Terminal Differentiationmentioning
confidence: 99%
“…In contrast, late addition of BIO (starting at day 5) completely abolished the expression of cardiac markers and the appearance of spontaneously contracting embryoid bodies [56]. Interestingly, the same compound BIO was identified in a HTS screen for small molecules that expand postnatal Isl1+ cardiovascular progenitor cells [58], and it was also shown to promote proliferation of neonatal and adult rat cardiomyocytes [59]. These intriguing results suggest that small molecule Wnt pathway activators like BIO may one day be used as pharmacological agents to restore function in the diseased heart.…”
Section: Small Molecules For Directing Stem Cell Differentiation Tmentioning
confidence: 96%